Watershed characteristics that are related to the occurrence of impaired (CWA 303(d)) waters for park units within the Pacific West Region of the National Park Service - Ling, Jia L., author; Laituri, Melinda, advisor; Loftis, Jim, committee member; Newman, Gregory, committee member (Colorado State University. Libraries, 2012)
Since the establishment of the Clean Water Act (CWA) in 1972, the federal government has made significant strides toward improving the quality of U.S. water resources. The Total Maximum Daily Load (TMDL) program created from the federal CWA distributed the responsibility for improving water quality to states, territories, and authorized tribes, while appointing the U.S. Environmental Protection Agency (EPA) as the lead oversight. Over 43,500 TMDL plans have been developed according to the EPA's national summary of TMDL information. However, implementation of TMDLs is often delayed, which hinders improvement in water quality and may reduce the restoration potential of an impaired waterbody. The National Park Service (NPS) is an important stakeholder in the TMDL program because restoring and preserving water quality for future uses and enjoyment is a vital component of its mission. Therefore, the goal of this study is to identify watershed characteristics that are relevant to the occurrence of impaired waters within watersheds that intersect park units. This will assist NPS managers in evaluating waterbodies at risk and restoration potential. An initial list of 25 watershed characteristics was identified to be included in this study. A survey was administered to NPS aquatic professionals to further reduce the number of characteristics and evaluate the most pertinent characteristics based on professional opinions. Eleven watershed characteristics were selected and quantified to examine their correlation to the occurrence of impaired waters. Watershed characteristics were chosen to represent each of the three categories: (1) land cover / use, (2) ecological / physical characteristics, and (3) social influences. The study area was limited to HUC 12 polygons that intersect park units within the Pacific West Region of NPS. Watershed characteristics and impairments were measured for all intersecting HUC 12 polygons. Impairments were assessed based on state listings of CWA 303(d) waters and categories 4a, 4b, and 4c of CWA Section 305(b). Linear regression analysis was employed to investigate the correlation between each watershed characteristic to percent impairment. The results of the analyses revealed that average slope, amount of hydrography, agricultural land cover, and forest land cover were significant indicators of impaired waters at alpha 0.10 level. Although many of the watershed characteristics may have synergistic effects, multicollinearity was not considered in the design of this study. However, the results of this study may guide water quality professionals to hone their efforts on actively managing the significant watershed characteristics identified in this study.
Keywords: national park service; watershed; water quality; total maximum daily load; CWA 303d; Clean Water Act